Enhancing the temperature sensing property of a Ca0.79−xBixEr0.01Yb0.2MoO4 phosphor via local symmetry distortion and reduction in non-radiative channels - Singh S.; Kachhap S.; Sharma M.; Singh S.K. (My University, 2025)
We demonstrate an enhancement in the upconversion (UC) emission and temperature sensing property of a CaMoO4:Er/Yb phosphor via distortion of the local symmetry environments and reduction in no-radiative channels. Bi3+ ion co-doping creates a local distortion while the average tetragonal structure of CaMoO4 remains intact. This creates asymmetry around the Er3+ ions which improves the UC emission. Furthermore, our calculations on XRD data show a reduction in the dislocation density and the micro-strain in the crystal with the introduction of Bi3+, which also favours the enhancement of UC emission as it reduces the non-radiative channels. Furthermore, the effect of this enhancement on the temperature sensing property of Er3+ ion has also been revealed. Our results show that the UC emission is enhanced about 25 times for Bi3+ co-doped samples which improves the temperature sensitivity significantly. The samples, both with and without Bi3+ co-doping, exhibited relative sensitivities of 0.0068 K−1 at 300 K and 0.0057 K−1 at 298 K which is a significant improvement and indicates the potential of the material for temperature sensing applications. This proof-of-concept provides a deeper understanding of the effect of Bi3+ doping on UC emission and opens new avenues for the development of high-performance temperature sensing materials. © 2023 The Royal Society of Chemistry.